Challenges Along The Academic Trajectory And Psychological Support To College Student: Contributions Of Two Community Service Projects - Pinheiro Ramos, Fabiana; Pereira Jardim, Adriano; Pantoja Gomes, Ana Carla; Nascimento Lucas, Juliana (Guará Journal, 2018)
Psychological  support  actions  are  described, developed  in  the  frame-work  of  two  Community Service  projects  executed  at  the  Psychology Department  of  Universidade  Federal  do  Espírito Santo:  Psychological  Screening  Project  and Psychological  Care  Service  for  Students.  The  actions aim  to  help  college  students  attended  by  the  Vice-Rectory  of  Student  Affairs  and  Citizenship  to  cope with  the  challenges  along  the  academic trajectory, in line with the institution’s student assistance policy. The activities involve psychological screening, individual attendance through psychotherapy and group workshops on the following themes: development of social skills: study orientation; and anxiety control and stress  coping.  From  2015  to  2017,  217  students participated,  mostly  fe-male, in their first year of higher education, who received some kind of grant  or  aid  and were  preferably  taking  their  first  to  third  term  in the morning  period.  In  total,  12  workshops  were  held and,  at  the  end,  the  students’ assessment appointed the importance of their learning. Thus, the community service projects contributed to overcome the difficulties the students faced along their academic trajectory, besides contributing to the education of community service students in Psychology by articulating teaching, research and community services.
Keywords: Student assistance; Psychological care; College students